PENINGKATAN KETERAMPILAN BERBICARA SISWA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS V SEKOLAH DASAR - Trisnadewi, Vidia; Halidjah, Siti; Margiati, K.Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTrisnadewi, Vidia. 2018. Improving Student Speaking Skills by Using Audio Visual Media in Vocational Class of Pontianak City Primary School. Essay. Primary School Teacher Education Study Program. Department of Primary Education, Faculty of Teacher Training and Education, University of Tanjungpura Pontianak. Advisor (I) Dr. Hj. Siti Halidjah, M.Pd., and Supervisor (II) Dra. K.Y. Margiati, M.Si.The common problem of this research,